The landscape of Rufford, 1700-1743: reconnecting archives with people and place - Law, Sarah (2016)
Despite growing recognition that the early eighteenth century was a period of flux in relation to gardening taste, the landscapes of elite estates of this period (with the exception of a few iconic gardens) have received little focussed attention. Moreover, the scholarship that exists has tended to isolate considerations of the core landscape of pleasure gardens and hall from its broader socio-economic and geographic contexts. This thesis aims to shed light on how more typical early eighteenth-century estate landscapes were understood through a case study of the everyday practices and local and national contexts which underpinned the development of the demesne landscape of the Rufford Estate, Nottinghamshire, during the ownership of Sir George Savile (1700-43).